معوِّقات استخدام نظم المعلومات المحاسبيَّة في عمليَّة اتِّخاذ القرارات الإداريَّة "دراسة ميدانيَّة على الشَّركات الصِّناعيَّة العاملة في السَّاحل السُّوري" - اسبر سعيد; علي عفراء (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف هذا البحث لاختبار مدى تأثير معوِّقات استخدام نظم المعلومات المحاسبيَّة (المعوِّقات المتعلِّقة بــ: متَّخذ القرار، نظم المعلومات المحاسبيَّة ذاتها، المؤسَّسة، البيئة الخارجيَّة) على استخدام هذه النُّظم في عمليَّة اتِّخاذ القرارات الإداريَّة، وذلك في عيِّنة من الشَّركات الصِّناعيَّة العاملة في السَّاحل السُّوري. للوصول لهدف البحث قام الباحثان بتوزيع (110) استبياناً على المديرين ورؤساء الأقسام والمراقبين وأفراد الكوادر الإداريَّة المسؤولة عن اتِّخاذ أشكال وأنواع مختلفة من القرارات المعتمد في اتِّخاذها على المعلومات المحاسبيَّة في الشَّركات عينة الدراسة، وقد بلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (90) استبانة. قام الباحثان بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 20). توصَّل الباحثان إلى مجموعة من الاستنتاجات وأهمّها: وجود تأثير معنوي لجميع المعوِّقات المدروسة، والمتعلقة بــ: متَّخذ القرار، نظم المعلومات المحاسبيَّة ذاتها، المؤسَّسة، البيئة الخارجيَّة على استخدام نظم المعلومات المحاسبيَّة في الشَّركات عينة الدراسة. فتمت التوصية بالعمل على زيادة المعرفة بنظم المعلومات المحاسبيَّة في الشَّركات عينة الدراسة من خلال الدَّورات التَّدريبيَّة وورش العمل بطرق حديثة تحاكي النَّمط الواقعي للمساهمة في بناء نظم فعَّالة توافق بيئة العمل. وضرورة تنمية الوعي بأهميَّة ومزايا استخدام نظم المعلومات المحاسبيَّة، والمواكبة المستمرة للمستجدَّات التِّقنيَّة في مجال نظم المعلومات المحاسبيَّة، زيادة مرونة الهيكل التَّنظيمي وتوفير التَّغذية العكسيَّة الرَّاجعة بالشَّكل المطلوب. The purpose of this research is to examine the effect of the obstacles to the use of accounting information systems (constraints which are related to the: decision maker, the accounting information systems itself, the institution, and external environment) on the use of these systems in the decision making process in a sample of industrial companies operating in the Syrian coast. To reach the goal of the research, the researchers distributed (110) questionnaires to managers, heads of departments, supervisors and administrative personnel responsible for taking various forms and types of decisions using the output of the accounting information systems in the companies which are research sample. The number of valid questionnaires that were discharged was (90). The researchers analyzed the data using the Statistical Analysis Program (SPSS 20). The researchers reached a number of conclusions, the most important of which are: There is a significant effect on all constraints (constraints related to: decision makers, the accounting information systems itself, the institution, and external environment. Depending on the research’s results, the researchers presented a set of recommendations, the most important of which were: To increase the knowledge of the accounting information systems in the companies which form the sample research through training courses and workshops in modern ways that mimic the realistic style of contributing to the construction of effective systems compatible with the work environment. The need to develop awareness of the importance and advantages of using accounting information systems, keeping abreast of the technical developments in accounting information systems, increasing the flexibility of the organizational structure and providing feedback in the required manner.